A Versatile Synthesis of β‐Lactam‐Fused Oxacycles through the Palladium‐Catalyzed Chemo‐, Regio‐, and Diastereoselective Cyclization of Allenic Diols. Issue 5 (2nd December 2014) - Alcaide, Benito; Almendros, Pedro; Carrascosa, Rocío; Casarrubios, Luis; Soriano, Elena
Abstract Chemo‐, regio‐ and stereocontrolled palladium‐catalyzed preparations of enantiopure morpholines, oxocines, and dioxonines have been developed starting from 2‐azetidinone‐tethered γ, δ‐, δ, ε‐, and ε, ζ‐allendiols. The palladium‐catalyzed cyclizative coupling reaction of γ, δ‐allendiols 2 with allyl bromide or lithium bromide was effective as 8‐endo cyclization by attack of the primary hydroxy group to the terminal allene carbon to afford enantiopure functionalized oxocines; whereas the palladium‐catalyzed cyclizative coupling reaction of 2‐azetidinone‐tethered ε, ζ‐allendiols 4 furnished dioxonines 16 through a totally chemo‐ and regioselective 9‐endo oxycyclization. By contrast, the palladium‐catalyzed cyclizative coupling reaction of 2‐azetidinone‐tethered δ, ε‐allendiols 3 with aryl and alkenyl halides exclusively generated six‐membered‐ring compounds 14 a and 15 a. These results could be explained through a 6‐exo cyclization by chemo‐ and regiospecific attack of the secondary hydroxy group to the internal allene carbon. Chemo‐ and regiocontrol issues are mainly influenced by the length of the tether rather than by the nature of the metal catalysts and substituents. This reactivity can be rationalized by means of density functional theory calculations.